2020
DOI: 10.1210/clinem/dgaa511
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis Contributes to the Imbalance of Treg and Th17 Cells in Graves’ Disease Patients by Propionic Acid

Abstract: Background Graves’ disease (GD) is a typical organ-specific autoimmune disease. Intestinal flora plays a pivotal role in immune homeostasis and autoimmune disease development. However, the association and mechanism between intestinal flora and GD remain elusive. Objective To investigate the association and mechanism between intestinal flora and GD. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 49 publications
5
102
0
Order By: Relevance
“…In addition to gut flora, SCFAs, the metabolic products of bacterial dietary fibre, affects Treg and Th17 cell differentiation (15,37). Our studies demonstrated that stigmasterol increases the abundance of Clostridia.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to gut flora, SCFAs, the metabolic products of bacterial dietary fibre, affects Treg and Th17 cell differentiation (15,37). Our studies demonstrated that stigmasterol increases the abundance of Clostridia.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we found at the genus level, high red meat intake significantly increased the relative abundance of Bacteroides and Alistipes genera in colon, but reduced the abundance of Lachnospiraceae_NK4A136 group, Faecalibaculum, Blautia, and Dubosiella genera. Previous studies have shown that the genera of Bacteroides and Alistipes can affect amino acid transport, metabolism, energy production and transport, and inflammation (34)(35)(36). Bacteroides can secret metalloprotease toxin both in vivo and in vitro (37), which stimulate the cleavage of intercellular adhesion protein E-cadherin in colonic epithelial cells, resulting in increased colonic mucosal permeability and activating NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell maturation in the intestinal tract occurs in the gut associated lymphoid tissue (GALT) and from there cells migrate to the intraepithelial layer or lamina propria. These T-cells are (31,33,34,36), and in human studies (16,(37)(38)(39). Supplementation with propionate enhances the activity and numbers of the anti-inflammatory Treg FoxP3 + cells and reduces the activity and numbers of Th17 and to a lesser extent Th1 pro-inflammatory T-cells via histone deacetylase inhibition (25,34,(40)(41)(42).…”
Section: Immune Regulation By Scfasmentioning
confidence: 99%
“…Nutritional components and microbial metabolites such as acetate, propionate, butyrate, tryptophan and phytoestrogens, act as immune regulators. Numerous studies demonstrate the action of propionate in regulating T-cell activity in vitro ( 33 35 ), in animal in vivo studies ( 31 , 33 , 34 , 36 ), and in human studies ( 16 , 37 39 ). Supplementation with propionate enhances the activity and numbers of the anti-inflammatory Treg FoxP3 + cells and reduces the activity and numbers of Th17 and to a lesser extent Th1 pro-inflammatory T-cells via histone deacetylase inhibition ( 25 , 34 , 40 42 ).…”
Section: Immune Regulation By Scfasmentioning
confidence: 99%